Duas mulheres em busca de si-Clarice Lispector e suas expressões sobre o patriarcalismo - Martins, Bruna Camêlo (Universidade Federal do Tocantins, 2022)
This paper aims to present the patriarchalism suffered by women in the Claricean tales, seeking thus to reflect about the patriarchal power under women in the nineteenth century, the silencing, the pursuit of freedom and the encounter of herself. The two short stories studied have important affinities, as they are women of approximate age and raised to serve, both seeking their freedom. Clarice's literature problematizes the situation of women in our society, and their daily struggle for the place of speech of women's subordination in our society, aiming at the representation of women in literature.